Identifikasi Metabolit Sekunder Ekstrak Etanol Belimbing Wuluh (Averrhoa bilimbi. L) - Fhadlyatul Khusna; Dhini Andriani; Fitrinaya Fitrinaya; Rifdah Rifdah; A. Ilmi Alfiana; Purnamasari Purnamasari; Friska Adelia Putri (JURNAL RISET RUMPUN MATEMATIKA DAN ILMU PENGETAHUAN ALAM, 2026)
Belimbing wuluh (Averrhoa bilimbi L.) is a medicinal plant known to contain various secondary metabolites, particularly flavonoids, which possess potential biological activities. This study aimed to isolate flavonoid compounds from the ethanol extract of belimbing wuluh fruit and determine the total flavonoid content. The research was conducted through sample preparation, ethanol extraction by maceration, solvent evaporation, liquid-liquid fractionation using n-hexane, ethyl acetate, and water, followed by phytochemical separation using column chromatography, preparative thin-layer chromatography, and two-dimensional thin-layer chromatography. The isolated fraction was further analyzed, and the total flavonoid content was determined using UV-Visible spectrophotometry with quercetin as the reference standard. The extraction process produced an extract yield of 22.70%, while solvent evaporation resulted in a concentrated extract with a yield of 8.8%. Fractionation indicated that the polar fraction was obtained in the highest proportion. Column chromatography generated 50 fractions with different color characteristics, indicating successful separation of compounds based on polarity. Thin-layer chromatography showed an Rf value of 0.4 in the ethyl acetate mobile phase, while preparative and two-dimensional thin-layer chromatography produced a single dominant band, suggesting a relatively pure isolate. The UV-Visible analysis showed excellent linearity and revealed a total flavonoid content of 230.76 mg QE/g or 23.08%, exceeding the minimum quality standard. These findings demonstrate that belimbing wuluh fruit is a promising natural source of flavonoids and has potential for further pharmaceutical and phytochemical development.